HEALTHCARE SEEKING BEHAVIOR IN MIDDLE-AGED ADULTS: THE SALIENCE OF RELIGIOUS COMMITMENT - Onyia, Sylvia (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Healthcare is an essential component of human existence, reflecting efforts to maintain and restore physical, mental, and emotional well-being. Past studies have underscored various constraints in healthcare-seeking behavior in Nigerian citizens. However, little is known about the role of religious commitment in healthcare. This study examined religious commitment as a predictor of healthcare-seeking behaviors in middle-aged adults. Two hundred and fifteen respondents randomly selected from various locations in the Enugu states participated in the study. They completed a self-report measure of health-seeking behavior and religious commitment inventory. The result of the regression analysis computed on the data demonstrated a statistically significant interaction between RC and HSB, F (1,213) = 31.63, p < 0.05. The adjusted R2 indicated that RC explained about 13.2% of the variation in HSB among middle-aged adults. The result implies the promotion of healthcare-seeking behavior in Nigeria.